Pengaruh Biochar Limbah Batang Jagung Terhadap Sifat Fisik Tanah Aluvial dan Produktivitas Bawang Merah (The Effect of Corn Stalks Biochar application on Physical Properties of Alluvial Soil and Productivity of Shallots) - Urifa Urifa; Cahyoadi Bowo (Fakultas Pertanian Universitas Borobudur, 2020)
Alluvial soil has great potential as a horticultural planting medium of shallots. Waste from corn stalks were used as biochar using pyrolysis techniques, applied to alluvial soils as a medium of planting shallots in a pot experiment. Application of biochar was 0 ton/ha (B0), 20 ton/ha (B1) and 40 ton/ha (B2) on alluvial soil from Mranggon Lawang village, Probolinggo, East Java. The results showed the biochar application did not show a significant effect on physical properties of the soil. The addition of biochar reduced the soil bulk density from 1.25 g/cm3 to 1.18 g/cm3 in the B2 sample, but increased the water need from 304,6 mm to 312,3 mm. The results of the experiment on plant indicators showed an increase in plant height, number of leaves, diameter of tubers and number of tubers with biochar application. Keywords: biochar, alluvial, shallots